Penentuan Jenis Longsoran Berdasarkan Arah Struktur di PT Indocement Tunggal Prakarsa Kuari A Desa Palimanan Kecamatan Gempol Kabupaten Cirebon Provinsi Jawa Barat - Haikal Fatwa Nugraha; Yuliadi Bejo; Iswandaru (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Indocement Tunggal Prakarsa is a mining company in Indonesia engaged in mining with limestone excavation materials. To support mining activities, it is necessary to conduct geotechnical studies. Mining geotechnics is the technical management of mining which includes investigation, sample testing, and management of geotechnical data as well as the application of recommendations for the geometry and dimensions of mine openings, and monitoring the stability of mine openings (Minister of Energy and Mineral Resources Decree No. 1827 K/30/MEM, 2018). One of the factors affecting slope stability is the presence of weak planes. In assessing a slope, kinematics analysis is one of the important methods. Kinematics analysis is an attempt to determine the stability of a slope based on the type of slope material movement without analyzing the force that causes the slope material to move (Gurocak et al., 2008). The purpose of this research is to determine the general direction of the structure and the type of failure potential that may occur in the study area. The results of the research obtained the general direction of the structure from the results of structural mapping in the field, namely for scanline 1 in the direction of N305°E/69° and N208°E/61°, scanline 2 in the direction of N5°E/74°, and scanline 3 in the direction of N334°E/62° and N264°E/77° and potential landslides that will be formed using stereographic projections, namely scanline 1 has a type of failure in the form of a wedge failure with an failure direction of N340°E, scanline 2 does not fulfill the landslide conditions because the direction of the slope and the direction of the dominant structure are perpendicular to each other, and scanline 3 has a type of failure in the form of a wedge failure with an failure direction of N58°E.Abstrak. PT Indocement Tunggal Prakarsa merupakan perusahaan tambang di Indonesia yang bergerak di bidang penambangan dengan bahan galian batu gamping. Untuk menunjang kegiatan penambangan perlu dilakukannya kajian geoteknik. Geoteknik tambang adalah pengelolaan teknis pertambangan yang meliputi penyelidikan, pengujian conto, dan pengelolaan data geoteknik serta penerapan rekomendasi geometri dan dimensi bukaan tambang, serta pemantauan kestabilan bukaan tambang (Kepmen ESDM No. 1827 K/30/MEM, 2018). Salah satu faktor yang mempengaruhi kestabilan lereng adalah terdapatnya bidang lemah. Dalam mengkaji sebuah lereng, analisis kinematika merupakan salah satu metode yang penting. Analisis kinematika merupakan upaya untuk mengetahui kestabilan dari suatu lereng yang didasarkan dari jenis gerakan material lereng tanpa menganalisis gaya penyebab material lereng tersebut bergerak (Gurocak dkk, 2008). Tujuan penelitian ini yaitu mengetahui arah umum struktur dan jenis potensi longsoran yang mungkin terjadi pada daerah penelitian. Hasil penelitian didapatkan arah umum struktur dari hasil pemetaan struktur dilapangan yaitu untuk scanline 1 berarah N305°E/69° dan N208°E/61°, scanline 2 berarah N5°E/74°, dan scanline 3 berarah N334°E/62° dan N264°E/77° dan potensi longsor yang akan terbentuk menggunakan proyeksi stereografis yaitu scanline 1 memiliki jenis longsoran berupa longsoran baji dengan arah longsoran N340°E, scanline 2 tidak terpenuhi syarat-syarat longsoran karena arah lereng dan arah struktur dominan yang saling tegak lurus, dan scanline 3 memiliki jenis longsoran berupa longsoran baji dengan arah longsoran N58°E.